An Exhaustive vision and Prospects of Content-Based Image Retrieval (International Journal of Communication Systems and Network Technologies, 2023)
Nowadays, work on digital images are gaining much popularity in the multimedia system, it becomes possible due to the rapid increase in the utilization of huge image database. Thus, the Content-Based Image Retrieval (CBIR) method has become the most valuable method for this purpose. This work mainly focuses on content-based image retrieval; which uses image features like color, shape, texture, etc. for searching the user query image from a large image database based on user request. CBIR is the most widely used technique as its searching capability is faster than the other traditional methods, and it works well in retrieving images automatically; it’s also a big alternative for the traditional method based approach. The CBIR techniques are used in many applications like surveillance detection, crime avoidance, fingerprint identification, E-library, medical, historical monument and biodiversity information systems and many more.
Keywords: CBIR; Feature Extraction; Shape; Texture, Tamura; Wavelet Transform; Performance Measure